2001
DOI: 10.1002/jso.1032
|View full text |Cite
|
Sign up to set email alerts
|

Instability of chromosome 8 as an indicator of aggressive tumor phenotype in pancreatic cancer

Abstract: These results suggest that the increased level of chromosomal instability may play a critical role in the development of aggressive tumor phenotype during pancreatic cancer progression. J. Surg. Oncol. 2001;76:181-187.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Furthermore, numerical imbalances for chromosome 8 are found more frequently in metastatic pancreatic carcinomas than in primary tumors [21]. Similar results were reported by Sato et al [22] who found that the majority of pancreatic cancer cell lines show numerical aberrations in chromosome 8 and these abnormalities are associated with malignant tumor growth. These findings suggest a possible involvement of gene(s) on chromosome 8 in the acquisition of aggressive phenotypes.…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, numerical imbalances for chromosome 8 are found more frequently in metastatic pancreatic carcinomas than in primary tumors [21]. Similar results were reported by Sato et al [22] who found that the majority of pancreatic cancer cell lines show numerical aberrations in chromosome 8 and these abnormalities are associated with malignant tumor growth. These findings suggest a possible involvement of gene(s) on chromosome 8 in the acquisition of aggressive phenotypes.…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, its overexpression-induced cell cycle arrest at the G1- to S-phase transition to inhibit human pancreatic cancer SW1990 cell proliferation [ 77 ]. KLF10 is located on chromosome 8q22, where mutations are quite frequent in pancreatic cancers [ 90 ]; however, mutational screening of a panel of the twenty-two human pancreatic cell lines showed no alteration in KLF10 expression [ 78 ].…”
Section: Role Of Klf10 As a Tumor Suppressor In Various Cancersmentioning
confidence: 99%
“…69 In contrast, instability of chromosome 8 and gains or amplifications of chromosome 8q24 have been previously associated with a poorer prognosis and a more aggressive tumor phenotype among PDAC patients as also found among our patients. 33,34,70 Despite this, the exact role of specific cancer-associated genes coded in this chromosomal region (eg, MYC ) in PDAC remains unclear. 71e74 Upregulation of MYC represents a hallmark of several different types of cancer 75 ; however, expression data from half of our cases revealed down-regulation of MYC in tumor versus inflammatory tissues, particularly among the patients harboring 8q24 gains.…”
Section: Figurementioning
confidence: 99%